Effects of precursor concentration and annealing temperature on CH3NH3PbI3 film crystallization and photovoltaic performance. (August 2017) - Zheng, Yan-Zhen; Lai, Xue-Sen; Luo, Yi; Zhao, Er-Fei; Meng, Fan-Li; Zhang, Xiang-Feng; Tao, Xia
Abstract: The ability to prepare homogeneous and highly crystalline planar perovskite films via the precise manipulation of a one-step solution-based crystallization process is still a key issue that hinders improvements to the ultimate photoelectric conversion efficiency (PCE) of devices. In this study, we prepared a series of planar CH3 NH3 PbI3 films using a chlorobenzene-assisted fast perovskite crystallization process with various precursor concentrations ranging from 30 to 50 wt% and subsequent annealing at 50–90 °C in order to investigate the effects of the precursor concentration and annealing temperature on crystallization and the photovoltaic performance. By precisely controlling the precursor concentration and annealing temperature, we obtained a homogeneous and highly crystalline planar perovskite film with high coverage under the optimized conditions (ca. 40 wt% and 70 °C), which led to sufficient light absorption and inhibited charge recombination, thereby yielding an enhanced PCE of 16.21%. Furthermore, the unsealed cell still retained a PCE of 10.98% after ambient air exposure for a period of 408 h. Graphical abstract: Highlights: Planar perovskite films were prepared via a one-step solution-process. Superior crystalline perovskite obtained by annealing temperature optimization. Uniform planar perovskite film was obtained by precise control of the concentration. A high photoelectric conversion efficiency of 16.21% was achieved.